Kemitraan Guru Dan Orang Tua Dalam Pembelajaran Quran Awal Bagi Anak Usia Dini - Imroatun, Imroatun; Utami, Sri Yulia; Inayah, Amellia (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2024)
The purpose of this study is to determine how parents and instructors may work together to help young children learn the Qur'an, as well as what obstacles need to be overcome. To map the dynamics of parent-teacher partnerships during the introduction and Qur'anic instruction. In this study, triangulation techniques, documentation, interviews, and observation was used as qualitative methodologies. The study's findings indicate that parent-teacher collaboration is crucial when it comes to introducing the Qur'an to children. Parents benefit immensely from having teachers in the classroom when it comes to educating their kids, particularly when it comes to teaching the Qur'an, and this can only be accomplished through strong parent-teacher cooperation. The partnership patterns implemented at RA Atouhiriyah include permanent, tentative, official, informal, and family partnership patterns.